Antiretroviral therapy and changing patterns of HIV stigmatization in Entebbe, Uganda - Russell, Steve; Zalwango, Flavia; Namukwaya, Stella; Katongole, Joseph; Muhumuza, Richard; Nalugya, Ruth; Seeley, Janet (John Wiley & Sons Ltd, 2015)
Antiretroviral therapy (ART) has the potential to change processes of HIV stigmatization. In this article, changing processes of stigmatization among a group of people living with HIV (PLWH) on ART in Wakiso District, Uganda, are analyzed using qualitative data from a study of PLWH’s self-management of HIV on ART. There were 38 respondents (20 women, 18 men) who had been taking ART for at least 1 year. They were purposefully selected from government and non-government ART providers. Two in depth interviews were held with each participant. Processes of reduced self-stigmatization were clearly evident, caused by the recovery of their physical appearance and support from health workers. However most participants continued to conceal their status because they anticipated stigma; for example, they feared gossip, rejection and their status being used against them. Anticipated stigma was gendered: women expressed greater fear of enacted forms of stigma such as rejection by their partner; in contrast men’s fears focused on gossip, loss of dignity and self-stigmatization. The evidence indicates that ART has not reduced underlying structural drivers of stigmatization, notably gender identities and inequalities, and that interventions are still required to mitigate and tackle stigmatization, such as counselling, peer-led education and support groups that can help PLWH reconstruct alternative and more positive identities. A video abstract of this article can be found at: https://youtu.be/WtIaZJQ3Y_8
Keywords: HIV; Stigma; Chronic illness; Developing countries; Doctor–patient communication/ interaction; Gender